What do we know about the experience of seclusion in a forensic setting? An integrative literature review. (20th May 2022) - Hansen, Alison; Hazelton, Michael; Rosina, Robyn; Inder, Kerry
Abstract: Seclusion is used in forensic and general mental health settings to protect a person or others from harm. However, seclusion can result in trauma‐related harm and re‐traumatization with little known about the experience of seclusion for consumers in forensic mental health settings from their perspectives. This article explores consumer experiences of seclusion in forensic mental health settings and explores the differences between female and male experiences of seclusion. Five electronic databases were systematically searched using keywords and variations of experience, attitude, seclusion, coercion, forensic mental health, and forensic psychiatry. Inclusion criteria were original peer‐reviewed studies conducted in adult forensic mental health settings reporting data on the experiences of or attitudes towards seclusion. Seven studies met the criteria for inclusion and a quality assessment was undertaken. Results found consumers in forensic mental health settings perceive seclusion to be harmful, a punishment for their behaviour, and largely a negative experience that impacts their emotional health. Some consumers report positive experiences of seclusion. Differences in the experience of seclusion for females and males are unclear. Further research is required to understand the experience of seclusion for women in forensic mental health settings. Identification and consideration of differences in the experience of seclusion for males and females may assist in identifying sex‐specific interventions and may inform policy and practices to eliminate or reduce the trauma associated with seclusion use.